Discrepancies in Recommendations on Pharmacokinetic Drug Interactions for Anticancer Medications and Direct Oral Anticoagulants (DOAC): A Comparative Analysis of Different Clinical Decision Support Systems and Sources - Karolina Nowinski; Roza Chaireti (Pharmaceuticals)
Background/objectives: In some cases of concomitant use of direct oral anticoagulants (DOAC) and certain anticancer medications, pharmacokinetic interactions are expected; however, clinical data is scarce. This report reviews the recommendations on the use of DOAC concurrently with anticancer drugs according to different clinical decision support systems and sources, with a focus on discrepancies. Methods: We reviewed the recommendations from the American Heart Association (AHA), European Heart Rhythm Association (EHRA), summary of product characteristics (SPC) in FASS (Swedish medicine information portal), the Swedish clinical decision support system Janusmed, and information from the Food and Drug Administration (FDA) on the concomitant use of apixaban, edoxaban, and rivaroxaban (activated factor X (FXa) inhibitors) and 80 anticancer drugs from 11 categories (240 drug pairs). Results: No warnings of expected pharmacokinetic drug interactions between FXa inhibitors and anticancer drugs were found for 155 drug pairs (65%) across all sources. The remaining 35% of drug pairs were flagged as having possible interactions with FXa inhibitors according to at least one source. Discrepancies in the recommendations from the different sources were reported. The reported discrepancies were, for the most part, associated with different assessments of the mechanism and the extent of pharmacokinetic interactions of each anticancer medication. Also, knowledge sources have different approaches to reporting potential interactions, in some cases reporting clinically relevant strictly pharmacokinetic interactions, whereas others include even patient-specific factors. Conclusions: The lack of clinical data and different recommendations can make clinical decisions on the concomitant use of DOAC and anticancer drugs difficult. Our compilation is meant to assist clinicians in making decisions based on the available evidence, even if it is scarce.